A kind of precision alumina ceramic and preparation method thereof

Through the combination technology of cationically modified alumina, sodium carboxylate modified graphene and alumina-coated silica, the problems of low density and thermal conductivity of alumina ceramics are solved, and the high density and thermal conductivity of high density and thermal conductivity are improved .

CN118791288BActive Publication Date: 2025-01-03苏州芯合半导体材料有限公司
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411277149.4
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-09-12
Publication Date
2025-01-03
Estimated Expiration
2044-09-12

AI Technical Summary

Technical Problem

Alumina ceramics have low density and strength properties, and their thermal conductivity needs to be improved.

Method used

The combination technology of cationically modified alumina, sodium carboxylate modified graphene and alumina-coated silica is used to form precision alumina ceramics with high density and excellent thermal conductivity through ultrasonic dispersion, ball milling and sintering processes.

Benefits of technology

The relative density, bending strength and thermal conductivity of alumina ceramics are significantly improved, and their physical and thermal physical properties are enhanced.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_3
    Figure SMS_3
  • Figure QLYQS_1
    Figure QLYQS_1
Patent Text Reader

Abstract

The invention belongs to the technical field of alumina ceramics, and discloses a precision alumina ceramic and a preparation method thereof; the precision alumina ceramic comprises 100 parts by weight of cation-modified alumina, 0.5-3 parts of sodium carboxylate-modified graphene, and 2-8 parts by weight of alumina-coated silicon dioxide; the surface of nano-alumina contains quaternary ammonium salt cations, which can electrostatically interact with sodium carboxylate anions on the surface of graphene, thereby enhancing the bonding strength between the nano-alumina and the surface of the graphene, enhancing the dispersibility in the alumina ceramic, and improving the reinforcing effect of the graphene; at the same time, after the nano-silica is coated with alumina, the compatibility with the alumina ceramic is better, and the relative density, bending strength, thermal conductivity and thermal conductivity of the ceramic are improved under the synergistic effect.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of alumina ceramics, and in particular relates to a precision alumina ceramic and a preparation method thereof. Background Art

[0002] Alumina ceramics have good wear resistance, corrosion resistance, mechanical strength, high temperature resistance and other properties, and are widely used in advanced ceramic products, anti-wear engineering, building materials, aerospace and other fields. Improving the strength, thermal conductivity and other properties of alumina ceramics can effectively expand its practical application areas. Adding inorganic additives such as silicon dioxide, silicon carbide, carbon fiber, graphene, etc. to alumina ceramics is an effective way to enhance the performance of alumina ceramics.

[0003] Surface modification of alumina is beneficial to improving the compactness, strength and other properties of alumina ceramics. The invention patent with publication number CN117303863A discloses alumina ceramics and its preparation method and application, which uses stearic acid as a modifier to form a self-stabilizing system with alumina, and then sand-mills, forms and sinters with yttrium-stabilized nano-zirconia. The obtained alumina ceramics have high density, hardness and fracture toughness, but the invention patent does not improve the thermal conductivity of alumina ceramics. Summary of the invention

[0004] The invention solves the problem of low density, strength and other properties of alumina ceramics.

[0005] The technical solution provided by the present invention is a precision alumina ceramic, comprising 100 parts by weight of cation-modified alumina, 0.5-3 parts by weight of sodium carboxylate-modified graphene, and 2-8 parts by weight of alumina-coated silica.

[0006] The preparation method of cationic modified alumina comprises: adding a solvent and nano-alumina into a reaction container, adding hexamethylene diisocyanate after ultrasonic dispersion, heating to a reaction temperature, stirring for a primary reaction, then adding hydroxypropyl quaternary ammonium salt, stirring for a secondary reaction, filtering after the reaction, washing the filter cake with dichloromethane, and drying to obtain cationic modified alumina.

[0007] The structural formula of hydroxypropyl quaternary ammonium salt is as follows: , n is 12-16.

[0008] The preparation method of sodium carboxylate modified graphene comprises: adding water into a reaction container, carboxylating graphene, adding sodium hydroxide aqueous solution after ultrasonic dispersion, adjusting the pH to 9-11, filtering, washing the filter cake with water, and drying to obtain sodium carboxylate modified graphene.

[0009] Preferably, the solvent is N,N-dimethylformamide or toluene.

[0010] Preferably, the masses of hexamethylene diisocyanate and hydroxypropyl quaternary ammonium salt are (80-150)% and (140-300)% of the mass of nano-aluminum oxide, respectively.

[0011] Preferably, the reaction temperature is 100-120° C., the time for the first reaction is 18-24 h, and the time for the second reaction is 24-36 h.

[0012] Preferably, the preparation method of alumina-coated silica includes: adding water and nano-silica into a reaction container, adding an aqueous solution of aluminum nitrate after ultrasonic dispersion, adding an aqueous solution of citric acid after stirring, adding ammonia water dropwise after stirring to adjust the pH to 8-9, stirring for 5-6 hours and then standing and aging for 12-18 hours to form a sol, which is then washed with water, dried and placed in a resistance furnace, heated to 550-700°C, and calcined for 3-5 hours to obtain alumina-coated silica.

[0013] Preferably, the mass of nano-silicon dioxide and citric acid is (15-35)% and (13-20)% of the mass of aluminum nitrate, respectively.

[0014] Preferably, the preparation method of hydroxypropyl quaternary ammonium salt comprises: adding acetonitrile, 3-dimethylamino-1-propanol and 1-bromoalkane in a molar ratio of 1:(1.2-1.3) into a reaction container, heating to 70-80°C, reacting for 24-36 hours, distilling the solution under reduced pressure, washing with methanol, and recrystallizing the product in dichloromethane to obtain hydroxypropyl quaternary ammonium salt.

[0015] Preferably, the structural formula of 1-bromoalkane is , n is 12-16.

[0016] Preferably, the preparation method of precision alumina ceramics includes: adding water, ethanol, and alumina-coated silica into a reaction container, adding cation-modified alumina and sodium carboxylate-modified graphene after ultrasonic dispersion, stirring for 2-4 hours, pouring the solution into a ball mill for ball milling for 6-10 hours, and then placing it in an oven to dry, and finally pressing the material into a green body, placing it in a vacuum sintering furnace, sintering, and cooling to obtain precision alumina ceramics.

[0017] Preferably, the sintering pressure is 10-15 MPa, the temperature is 1300-1500° C., and the sintering time is 2-3 h.

[0018] The technical effect of the present invention is that the present invention uses hexamethylene diisocyanate to react with the hydroxyl group on the surface of nano-alumina to introduce isocyanate groups, and then reacts with the hydroxyl group of hydroxypropyl quaternary ammonium salt to obtain cationic modified alumina. After the surface organic modification, the dispersibility of alumina is better, which is conducive to improving the uniformity of alumina ceramics, improving compactness, and increasing relative density.

[0019] The surface of the nano-alumina of the present invention contains quaternary ammonium salt cations, which can electrostatically interact with the sodium carboxylate anions on the surface of graphene, thereby enhancing the bonding strength between the nano-alumina and the surface of the graphene, enhancing the dispersibility in the alumina ceramic, and improving the reinforcing effect of the graphene; at the same time, after the nano-silicon dioxide is coated with alumina, it has better compatibility with the alumina ceramic, and under the synergistic effect, the relative density, bending strength, thermal conductivity and thermal conductivity of the ceramic are improved. DETAILED DESCRIPTION

[0020] The technical scheme of the present invention is further illustrated by specific examples below. It should be understood by those skilled in the art that the embodiments are only to help understand the present invention and should not be regarded as specific limitations of the present invention. Unless otherwise defined, all technical and scientific terms used in the present invention have the same meaning as those commonly understood by those skilled in the art of the present invention. The terms used in the specification of the present invention are only for the purpose of describing specific embodiments and are not intended to limit the present invention.

[0021] The nano-alumina of the present invention has an average particle size of 400nm; the average particle size of the nano-silicon dioxide is 40nm.

[0022] Graphene, diameter is 0.5~3μm and thickness is 0.55-1.2nm.

[0023] Add 30 mL of 98% concentrated sulfuric acid and 500 mg of graphene into the reaction container, add 10 mL of concentrated nitric acid after ultrasonic dispersion, heat to 140°C, stir for 1 hour, add water to dilute, filter, wash with water, and dry to obtain carboxylated graphene.

[0024] Example 1

[0025] (1) Add 40 mL of acetonitrile, 30 mmol of 3-dimethylamino-1-propanol, and 39 mmol of 1-bromohexadecane into a reaction vessel, heat to 80°C, react for 24 hours, distill the solution under reduced pressure, wash with methanol, and recrystallize the product in dichloromethane to obtain hydroxypropyl quaternary ammonium salt.

[0026] (2) Add 2L N,N-dimethylformamide solvent and 50g nano-alumina into the reaction container, add 40g hexamethylene diisocyanate after ultrasonic dispersion, heat to 110°C, stir and react for 18h, then add 60g hydroxypropyl quaternary ammonium salt, stir and react for 24h, filter, wash the filter cake with dichloromethane, and dry to obtain cationic modified alumina.

[0027] (3) Add 3 L of water and 20 g of carboxylated graphene to the reaction container, add sodium hydroxide aqueous solution after ultrasonic dispersion, adjust the pH to 11, filter, wash the filter cake with water, and dry to obtain sodium carboxylate modified graphene.

[0028] (4) Add 600 mL of water and 6 g of nano-silica into the reaction container, add 80 mL of an aqueous solution containing 40 g of aluminum nitrate after ultrasonic dispersion, add 50 mL of an aqueous solution containing 5.2 g of citric acid after stirring, add ammonia water dropwise after stirring to adjust the pH to 9, stir for 5 h, let stand for 18 h to form a sol, then wash with water, dry, place in a resistance furnace, heat to 700 ° C, and calcine for 3 h to obtain alumina-coated silica.

[0029] (5) Add 1L of water, 1L of ethanol, 80g of alumina-coated silica into the reaction vessel, add 1000g of cation-modified alumina and 5g of sodium carboxylate-modified graphene after ultrasonic dispersion, stir for 3h, pour the solution into a ball mill and ball mill for 10h, then place it in an oven to dry, and finally press the material into a green body, place it in a vacuum sintering furnace, raise the temperature to 1500℃ at 10MPa, sinter for 2h, and cool to obtain precision alumina ceramics.

[0030] Example 2

[0031] (1) Add 30 mL of acetonitrile, 30 mmol of 3-dimethylamino-1-propanol, and 36 mmol of 1-bromododecane to a reaction vessel, heat to 70°C, react for 36 hours, distill the solution under reduced pressure, wash with methanol, and recrystallize the product in dichloromethane to obtain hydroxypropyl quaternary ammonium salt.

[0032] (2) Add 3L toluene solvent and 50g nano-alumina into the reaction container, add 75g hexamethylene diisocyanate after ultrasonic dispersion, heat to 100°C, stir and react for 24h, then add 150g hydroxypropyl quaternary ammonium salt, stir and react for 36h, filter, wash the filter cake with dichloromethane, and dry to obtain cationic modified alumina.

[0033] (3) Add 4 L of water and 20 g of carboxylated graphene to a reaction container, add sodium hydroxide aqueous solution after ultrasonic dispersion, adjust the pH to 9, filter, wash the filter cake with water, and dry to obtain sodium carboxylate-modified graphene.

[0034] (4) Add 800 mL of water and 14 g of nano-silica to a reaction container. After ultrasonic dispersion, add 80 mL of an aqueous solution containing 40 g of aluminum nitrate. After stirring, add 50 mL of an aqueous solution containing 8 g of citric acid. After stirring, add dropwise ammonia water to adjust the pH to 9. After stirring for 6 h, allow to stand for 12 h to form a sol. The sol is then washed with water, dried, and placed in a resistance furnace. The temperature is raised to 550 ° C. The solution is kept warm and calcined for 5 h to obtain alumina-coated silica.

[0035] (5) Add 1.5 L of water, 1.5 L of ethanol, and 5 g of alumina-coated silica into the reaction vessel. After ultrasonic dispersion, add 1000 g of cation-modified alumina and 18 g of sodium carboxylate-modified graphene. Stir for 2 h. Pour the solution into a ball mill and mill for 6 h. Then place it in an oven to dry. Finally, press the material into a green body, place it in a vacuum sintering furnace, raise the temperature to 1300 °C at 10 MPa, sinter for 3 h, and cool to obtain precision alumina ceramics.

[0036] Example 3

[0037] (1) Add 30 mL of acetonitrile, 30 mmol of 3-dimethylamino-1-propanol, and 36 mmol of 1-bromotetradecane to a reaction vessel, heat to 75°C, react for 36 hours, distill the solution under reduced pressure, wash with methanol, and recrystallize the product in dichloromethane to obtain hydroxypropyl quaternary ammonium salt.

[0038] (2) Add 3L N,N-dimethylformamide solvent and 50g nano-alumina into the reaction container, add 60g hexamethylene diisocyanate after ultrasonic dispersion, heat to 120°C, stir and react for 18h, then add 110g hydroxypropyl quaternary ammonium salt, stir and react for 36h, filter, wash the filter cake with dichloromethane, and dry to obtain cationic modified alumina.

[0039] (3) Add 3 L of water and 20 g of carboxylated graphene to a reaction container, add sodium hydroxide aqueous solution after ultrasonic dispersion, adjust the pH to 10, filter, wash the filter cake with water, and dry to obtain sodium carboxylate modified graphene.

[0040] (4) Add 700 mL of water and 10 g of nano-silica to the reaction container, add 80 mL of an aqueous solution containing 40 g of aluminum nitrate after ultrasonic dispersion, add 50 mL of an aqueous solution containing 6.5 g of citric acid after stirring, add ammonia water dropwise after stirring to adjust the pH to 8, stir for 6 h, let stand and age for 12 h to form a sol, then wash with water, dry, place in a resistance furnace, heat to 600 ° C, and calcine for 5 h to obtain alumina-coated silica.

[0041] (5) Add 1.5L of water, 1.5L of ethanol, and 20g of alumina-coated silica into a reaction vessel, add 1000g of cation-modified alumina and 30g of sodium carboxylate-modified graphene after ultrasonic dispersion, and stir for 4h. Pour the solution into a ball mill and carry out ball milling for 6h. Then place it in an oven to dry. Finally, press the material into a green body, place it in a vacuum sintering furnace, raise the temperature to 1300°C at 15MPa, sinter for 2h, and cool to obtain precision alumina ceramics.

[0042] Comparative Example 1

[0043] (1) Add 1L of water, 1L of ethanol, and nano-alumina into the reaction container and stir for 3 hours. Pour the solution into a ball mill and ball mill for 10 hours. Then place it in an oven to dry. Finally, press the material into a green body and place it in a vacuum sintering furnace. Heat it to 1500°C at 10MPa, sinter it for 2 hours, and cool it to obtain precision alumina ceramics.

[0044] Comparative Example 2

[0045] The difference between this comparative example and Example 1 is that unmodified nano-alumina is added.

[0046] (1) Add 1L of water, 1L of ethanol, 80g of alumina-coated silica into a reaction vessel, add 1000g of nano-alumina and 5g of sodium carboxylate-modified graphene after ultrasonic dispersion, stir for 3h, pour the solution into a ball mill and ball mill for 10h, then place it in an oven to dry, and finally press the material into a green body, place it in a vacuum sintering furnace, heat it to 1500℃ at 10MPa, sinter it for 2h, and cool it to obtain precision alumina ceramics.

[0047] Comparative Example 3

[0048] The difference between this comparative example and Example 1 is that no alumina-coated silica is added.

[0049] (1) Add 1L of water, 1L of ethanol, 1000g of cation-modified alumina, and 5g of sodium carboxylate-modified graphene into a reaction container and stir for 3h. Pour the solution into a ball mill and mill it for 10h. Then place it in an oven to dry. Finally, press the material into a green body and place it in a vacuum sintering furnace. Heat it to 1500℃ at 10MPa, sinter it for 2h, and cool it to obtain precision alumina ceramics.

[0050] Comparative Example 4

[0051] The difference between this comparative example and Example 1 is that nano-silicon dioxide not coated with alumina is added.

[0052] (1) Add 1L of water, 1L of ethanol, 80g of nano-silica into a reaction container, add 1000g of cation-modified alumina and 5g of sodium carboxylate-modified graphene after ultrasonic dispersion, stir for 3h, pour the solution into a ball mill and ball mill for 10h, then place it in an oven to dry, and finally press the material into a green body, place it in a vacuum sintering furnace, heat it to 1500℃ at 10MPa, sinter it for 2h, and cool it to obtain precision alumina ceramics.

[0053] Comparative Example 5

[0054] The difference between this comparative example and Example 1 is that no sodium carboxylate-modified graphene is added.

[0055] (1) Add 1L of water, 1L of ethanol, and 80g of alumina-coated silica into a reaction vessel, add 1000g of cationic modified alumina after ultrasonic dispersion, stir for 3h, pour the solution into a ball mill and ball mill for 10h, then place it in an oven to dry, and finally press the material into a green body, place it in a vacuum sintering furnace, heat it to 1500℃ at 10MPa, sinter it for 2h, and cool it to obtain precision alumina ceramics.

[0056] Comparative Example 6

[0057] The difference between this comparative example and Example 1 is that unmodified graphene is added.

[0058] (1) Add 1L of water, 1L of ethanol, and 80g of alumina-coated silica into a reaction vessel, add 1000g of cation-modified alumina and 5g of graphene after ultrasonic dispersion, and stir for 3h. Pour the solution into a ball mill and ball mill for 10h, then place it in an oven to dry, and finally press the material into a green body, place it in a vacuum sintering furnace, heat it to 1500℃ at 10MPa, sinter it for 2h, and cool it to obtain precision alumina ceramics.

[0059] The relative density of alumina ceramic samples was tested according to the Archimedes method. Each sample was tested 5 times and the average value was taken.

[0060] According to GB / T 39862-2021 method, the thermal conductivity of alumina ceramic samples was tested. Each sample was tested 3 times and the average value was taken.

[0061] The three-point bending method was used to test the flexural strength of alumina ceramic samples. The sample size was 35 mm × 4 mm × 3 mm, and the loading rate was 0.5 mm / min.

[0062] Table 1 Alumina ceramic performance test

[0063]

[0064] As shown in Table 1, compared with Comparative Example 1, the alumina ceramic samples of Examples 1-3 have a greater relative density, better compactness, a large thermal conductivity, high flexural strength, and better thermal conductivity and mechanical properties. This is attributed to the surface modification of nano-alumina using hexamethylene diisocyanate and hydroxypropyl quaternary ammonium salt, which improves the dispersibility of nano-alumina, is conducive to improving the uniformity of alumina ceramics, and the surface of nano-alumina contains quaternary ammonium salt cations, which can electrostatically interact with sodium carboxylate anions on the surface of graphene, enhance the bonding strength between nano-alumina and the surface of graphene, enhance the dispersibility in alumina ceramics, and improve the reinforcing effect of graphene; at the same time, after nano-silicon dioxide is coated with alumina, it has better compatibility with alumina ceramics, and the relative density, thermal conductivity and flexural strength of the ceramics are improved under the synergistic effect.

[0065] In Comparative Example 2, unmodified nano-alumina is added, which has poor dispersibility and cannot interact with sodium carboxylate-modified graphene. The interface bonding strength between the two is low, and the reinforcing effect of graphene is poor, resulting in low relative density, thermal conductivity and flexural strength of the alumina ceramic.

[0066] In Comparative Example 3, no alumina-coated silica was added, and the flexural strength of the alumina ceramic was significantly lower than that of Example 1.

[0067] Comparative Example 4 adds uncoated modified nano-silica, which has poor compatibility with alumina ceramics, and the two are prone to phase separation defects, affecting the flexural strength of the ceramics.

[0068] In Comparative Example 5, no sodium carboxylate-modified graphene was added, and the thermal conductivity and flexural strength of the alumina ceramic were significantly lower than those in Example 1.

[0069] In Comparative Example 6, ordinary graphene is added, which cannot interact with the cation-modified alumina. The interface bonding strength between the two is low, and the reinforcing effect of graphene is poor, resulting in the thermal conductivity and flexural strength of the alumina ceramic being lower than those in Example 1.

[0070] The above-mentioned embodiments only express several implementation methods of the present invention, and the descriptions thereof are relatively specific and detailed, but they cannot be understood as limiting the scope of the invention patent. It should be pointed out that, for ordinary technicians in this field, several variations and improvements can be made without departing from the concept of the present invention, and these all belong to the protection scope of the present invention. Therefore, the protection scope of the patent of the present invention shall be subject to the attached claims.

Claims

1. A precision alumina ceramic, characterized in that: The precision alumina ceramic comprises 100 parts by weight of cation-modified alumina, 0.5-3 parts of sodium carboxylate-modified graphene, and 2-8 parts by weight of alumina-coated silicon dioxide; The preparation method of the cationic modified alumina comprises: adding a solvent and nano-alumina into a reaction container, adding hexamethylene diisocyanate after ultrasonic dispersion, heating to a reaction temperature, stirring for a primary reaction, then adding hydroxypropyl quaternary ammonium salt, stirring for a secondary reaction, filtering after the reaction, washing, and drying to obtain the cationic modified alumina; The mass of the hexamethylene diisocyanate and hydroxypropyl quaternary ammonium salt is 80-150% and 140-300% of the mass of the nano-alumina, respectively; The structural formula of the hydroxypropyl quaternary ammonium salt is as follows: , n is 12-16; The preparation method of sodium carboxylate modified graphene comprises: adding water to a reaction container, carboxylating graphene, adding sodium hydroxide aqueous solution after ultrasonic dispersion, adjusting the pH to 9-11, filtering, washing, and drying to obtain sodium carboxylate modified graphene; The preparation method of alumina-coated silica comprises: adding water and nano-silica into a reaction container, adding an aqueous solution of aluminum nitrate after ultrasonic dispersion, adding an aqueous solution of citric acid after stirring, adding ammonia water dropwise after stirring to adjust the pH to 8-9, stirring for 5-6 hours and then standing and aging for 12-18 hours to form a sol, washing, drying, placing in a resistance furnace, heating to 550-700° C., and calcining at the temperature for 3-5 hours to obtain alumina-coated silica.

2. The precision alumina ceramic according to claim 1, characterized in that: The solvent is N,N-dimethylformamide or toluene.

3. The precision alumina ceramic according to claim 1, characterized in that: The reaction temperature is 100-120° C., the time for the first reaction is 18-24 hours, and the time for the second reaction is 24-36 hours.

4. The precision alumina ceramic according to claim 1, characterized in that: The masses of the nano-silicon dioxide and citric acid are respectively (15-35)% and (13-20)% of the mass of aluminum nitrate.

5. The precision alumina ceramic according to claim 1, characterized in that: The preparation method of the hydroxypropyl quaternary ammonium salt comprises: adding acetonitrile, 3-dimethylamino-1-propanol and 1-bromoalkane in a molar ratio of 1:(1.2-1.3) into a reaction container, heating to 70-80° C., reacting for 24-36 hours, distilling the solution under reduced pressure, washing, and recrystallizing to obtain the hydroxypropyl quaternary ammonium salt.

6. The precision alumina ceramic according to claim 5, characterized in that: The structural formula of the 1-bromoalkane is , n is 12-16.

7. A method for preparing the precision alumina ceramics according to any one of claims 1 to 6, characterized in that: The method for preparing precision alumina ceramics comprises: adding water, ethanol, and alumina-coated silica into a reaction container, adding cation-modified alumina and sodium carboxylate-modified graphene after ultrasonic dispersion, stirring for 2-4 hours, pouring the solution into a ball mill for ball milling for 6-10 hours, and then placing it in an oven for drying, and finally pressing the material into a green body, placing it in a vacuum sintering furnace, sintering, and cooling to obtain precision alumina ceramics.

8. The method for preparing precision alumina ceramics according to claim 7, characterized in that: The sintering process is performed under a pressure of 10-15 MPa, a temperature of 1300-1500° C. and a time of 2-3 hours.